Development Of NGO Governance In Malaysia: Lessons From Indonesia And Jordan - Mohd Faridh Hafez Mhd Omar; Sharifah Hayaati Syed Ismail (Usuli Faqih Research Centre PLT, 2024)
Malaysia is highly recognized as a developing country and thus progressive in calling the third sector (NGO) to participate in policy making and policy implementation. The idea of good governance practices has become increasingly important not only for the public sector but not for the NGO sector. Good governance aspect is significantly important in discussing the NGO development over leakage factor, abuse of power, corruption, accountability and others in which will be the objective of this paper’s discussion. Therefore, the introduction of five codes of governance for Malaysian NGO is the latest step implemented by the government to assess the performance of NGO to relate to its efficiency and effectiveness. At the same time, Indonesia and Jordan also offer great lessons. By utilizing descriptive and comparative methods, and making a great deal of comparison to Indonesia and Jordan, this article found that Malaysian NGOs’ involvement in governance practice has recently received great attention.